Rise and fall of competitiveness in individualistic and collectivistic societies - Leibbrandt, Andreas; Gneezy, Uri; List, John A (Proceedings of the National Academy of Sciences - PNAS, 2013)
Competitiveness pervades life: plants compete for sunlight and water, animals for territory and food, and humans for mates and income. Herein we investigate human competitiveness with a natural experiment and a set of behavioral experiments. We compare competitiveness in traditional fishing societies where local natural forces determine whether fishermen work in isolation or in collectives. We find sharp evidence that fishermen from individualistic societies are far more competitive than fishermen from collectivistic societies, and that this difference emerges with work experience. These findings suggest that humans can evolve traits to specific needs, support the idea that socio-ecological factors play a decisive role for individual competitiveness, and provide evidence how individualistic and collectivistic societies shape economic behavior.